How are whole-school mental health programmes evaluated? A systematic literature review. (3rd April 2022) - Wignall, Alice; Kelly, C.; Grace, P.
ABSTRACT: The prevalence of mental health and emotional well-being difficulties in children is increasing, and schools play a key role in addressing this. Whole-school approaches have been suggested as an effective way of supporting children's mental health and well-being; however, there appears to be no consistent approach to their evaluation, and research, to date, has reported varying levels of measurable impact. The present study provides a systematic literature review of how whole-school mental health programmes have been evaluated, between 2003 and 2017, focusing on the outcomes measured and methodologies used. Within the 14 evaluations reviewed, a wide range of outcomes were measured, with most concentrating on the impact on the child rather than wider whole-school effects. Questionnaires were the most popular method of evaluation, with some researchers using interviews and archival data to inform conclusions. Findings suggest that there appears to be a lack of clarity about how whole-school mental health programmes are evaluated, and which outcomes are used in order to measure effective implementation and impact on children's emotional well-being. The validity of existing evaluations is questioned, as many factors of these multi-faceted programmes were not measured and their adaptable nature makes effective evaluation complex. The review concludes that a bespoke, flexible approach to programme evaluation is necessary to capture the depth and breadth of programme impact, and also that qualitative approaches may allow researchers to explore perceived impact and implementation practice of whole-school mental health approaches in more depth.